Enhancing Fine Motor Skills Through Project-Based Learning: A Beading Intervention for Kindergarten Children with Learning Difficulties - Nuur, Dwi Mulyanti; Chamidah, Atien Nur (Papanda Publisher, 2025)
Fine motor skills development represents a critical foundation for academic readiness in early childhood, yet children with learning difficulties often experience significant challenges in this domain. This study investigated the effectiveness of project-based learning through beading activities in enhancing fine motor skills among kindergarten children with learning difficulties. A classroom action research design following the Kemmis and McTaggart model was employed, involving three children aged 4-5 years from TK Negeri 1 Kecamatan Kaliorang who demonstrated fine motor developmental challenges. The intervention was implemented across two cycles, each consisting of three sessions featuring structured beading activities using various materials including straws, beads, and string. Data collection utilized systematic observation with a seven-indicator assessment tool measuring tool handling, object manipulation, threading skills, pattern arrangement, and hand-eye coordination. Pre-test results revealed that no children achieved mastery levels, with an average completion rate of 52.4%. Following Cycle I implementation, completion rates increased to 71.4% with one child (33.3%) achieving mastery. After strategic modifications in Cycle II, including simplified instructions and enhanced materials, dramatic improvements were observed with completion rates reaching 93.3% and all three children (100%) achieving mastery levels. Qualitative observations indicated enhanced motivation, enthusiasm, and self-confidence throughout the intervention. The findings demonstrate that project-based learning through beading activities significantly improves fine motor skills in children with learning difficulties. The systematic, scaffolded approach provides valuable insights for early childhood educators seeking evidence-based interventions for inclusive learning environments.